Billing and collections : - Bragg, Steven M. (John Wiley & Sons, 2005)
Billings and Collections Best Practices offers advice for implementing a plethora of best practices to greatly improve your company's level of efficiency in information reporting, including: Showing you how to create a more efficient billing operation; Demonstrating how you can reduce the error rate on bills sent to customers; Revealing specific steps for you to reduce the amount of outstanding receivables; Providing guidelines on how you can restructure invoice formats to shorten the payment interval; Detailing how to create a database for recurring billings and how to maintain its accuracy.